PENGARUH KONDISI SOSIAL EKONOMI KELUARGA TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN PENDIDIKAN ( SUATU STUDI DI KECAMATAN PULUTAN KABUPATEN KEPULAUAN TALAUD ) - LANGINAN, SUSANTRI; TULUSAN, FEMMY; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2014)
There is still encountered a problem with the education system in Indonesia isone of the basic education age children are no longer able to continue to secondary school levelMany factors affect the condition. The main factor which used to be the reason the people are:the high cost of education and still less attention to the importance of parental education forchildren in the district mereka.Masyarakat Pulutan have a serious problem in the field ofeducation it is reflected from the number of people who just graduated elementary school (SD)and junior high school course. A lot of people who did not complete primary education indicatethat the low participation rate in education.This study aims to determine the effect of socio-economic conditions of people'sparticipation in the construction of this pendidikan.Penelitian took place in the District PulutanTalaud Islands and type of study is a quantitative study with a sample of 63 respondents / HeadFamily.The result is that the opinion of the respondents / communities in the District Pulutan onsocio-economic conditions (X) the average - average in the category of "medium" or moderatewhich is equal to 68.25% of the 63 respondents there, which is categorized as "low" assessmentby 17, 48% and were categorized "high" only about 14.29%. And community participation ineducation development (Y) Average - average still is in the category "medium" which is equal to50.79% of the 63 respondents, categorized as 'low' judgment as much as 22.22% andcategorized "high" of about 26 , 99%. As the results of the study it can be stated that the socioeconomicconditions have a significant influence on people's participation in educationdevelopment.Key words: social economic conditions, community participation, Education development